Preparation and characterization of self-photostabilizing UV-durable bionanocomposite membranes for outdoor applications - Kushwaha, Omkar S.; Avadhani, C. V.; Singh, R. P. (Carbohydrate Polymers, 2015)
Here, we report a durable and ultraviolet (UV) resistant nanocomposite membrane of chitosan (CS) with effective photostabilization ascribed to Zinc oxide (ZnO) nanoparticles. Zinc oxide nanoparticles were successfully dispersed in the solution of chitosan polymer. The nanocomposite films with the homogenous dispersion of ZnO nanoparticles in the chitosan matrix were obtained by solution casting method and the influence of ZnO nanoparticles as a photostabilizer was studied. The nanocomposite membranes were photoirradiated by polychromatic radiations with lambda > 300 nm using mercury vapour lamps in SEPAP instrument. The resulting nanocomposite material exhibited excellent UV-resistance in very low percentages of ZnO nanoparticles. The chitosan membranes showed fast degradation attributes than the nanocomposite membranes. ZnO nanoparticles effectively absorbed UV radiations, thus protecting polymer from radiation degradation. The neat and irradiated nanocomposites of chitosan and ZnO nanoparticles (CS/ZnO) were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy for the chemical changes/degradation taking place. Chitosan nanocomposites were further characterized for tensile properties, contact angle measurements and surface morphology. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bionanocomposite membrane; Chitosan; Contact angle measurement; Fourier transform infrared spectroscopy; Photostabilization; Zinc oxide nanoparticles